The Effect of Hypnoteaching Intervention Methods on Interest in Reading Story Texts - Pirman Pirman (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2024)
The purpose of this study is to analyze the correlation and influence between the Hypnoteaching method and the interest in reading story texts in MIN 1 Bogor students. The study is experimental research using the True experimental design model and a posttest-only control design approach. The analysis was carried out based on questionnaire data that was disseminated and interpreted through descriptive analysis and inferential analysis to describe the influence of the two research variables. The data obtained is processed through; 1) descriptive analysis to describe one of the variables with a percentage value. 2) Inferential statistical analysis is used to see correlations using the Product Moment formula. 3) Then, a differential test was carried out using t-test statistics to determine the effect. The results of this study showed that the results of the paired simple test using SPSS version 27 showed that the significance value was 0.001 < 0.05 which means that there was an average questionnaire about the interest in reading story texts using the Hypnoteaching intervention method. It can be concluded that there is an effect of the use of Hypnoteaching intervention methods on the interest in reading story texts in MIN 1 Bogor Regency students.